Values of Character in Sport (Study on Student's Pencak Silat) - Andi Sultan Brilin Susandi E.W; Muh. Ismail; Nyoman Sukrawan (Universitas Negeri Medan, 2020)
In fact, current education has not been able to achieve its goals optimally. Especially related to issues of noble character and character. Pencak silat as a sport is assumed to have many noble values that can make students' character change for the better. The problem in this study are what are the character values contained in the sport of pencak silat? The collection technique and research instruments include observation sheets and unstructured interviews. The population in this study were all athletes of martial arts students at SMANOR Palu Central Sulawesi. The sampling technique used a quota sampling technique. Data analysis techniques include: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the character values that exist in the sport of martial arts include religious, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the country, respect for achievement, friendly/communicative, love peace, love to read, care about the environment, care about social, and responsibility